2005
DOI: 10.1136/gut.2005.064030
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete screening flexible sigmoidoscopy associated with female sex, age, and increased risk of colorectal cancer

Abstract: Background: Several previous studies have found that females and older individuals are at greater risk of having incomplete flexible sigmoidoscopy. However, no prior study has reported the subsequent risk of colorectal cancer (CRC) following incomplete sigmoidoscopy. Methods: Using data from 55 791 individuals screened as part of the Colon Cancer Prevention (CoCaP) programme of Kaiser Permanente of Northern California, we evaluated the likelihood of having an inadequate (,40 cm) examination by age and sex, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…For example, our data suggest that the duration of low risk of distal CRC after a negative sigmoidoscopy is longer among younger individuals. Also, there is a growing body of research implicating various endoscopy quality indicators, such as depth of insertion,21 adenoma detection rate38 39 and endoscopist specialty (which may serve as a proxy for quantity/quality of endoscopist training),32 38 40–42 with the occurrence of CRC after endoscopy. Therefore, the absolute risk and patterns of CRC incidence postendoscopy could differ in different populations and healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our data suggest that the duration of low risk of distal CRC after a negative sigmoidoscopy is longer among younger individuals. Also, there is a growing body of research implicating various endoscopy quality indicators, such as depth of insertion,21 adenoma detection rate38 39 and endoscopist specialty (which may serve as a proxy for quantity/quality of endoscopist training),32 38 40–42 with the occurrence of CRC after endoscopy. Therefore, the absolute risk and patterns of CRC incidence postendoscopy could differ in different populations and healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Using the CoCaP database, we previously defined a cohort of 72 483 KPNC members who had a screening sigmoidoscopy negative for both polyps and cancer between 1994 and 1996; approximately 80% of the total number of those screened were included based on their negative exam 21. Cohort inclusion and exclusion criteria, and cancer incidence during the first 5 years after negative sigmoidoscopy have previously been described 20.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, those with inadequate FS (particularly if due to discomfort) were more likely to have inadequate FS at repeat examination (OR: 6.24; 95% CI: 5.77–6.75), underscoring the importance of offering sedation to the patient or switching to another screening modality. Inadequate FS has also been associated with subsequent CRC [63]. It is important for patients and providers to strive to ensure an adequate FS at the first screening attempt.…”
Section: The Challenges After Fs Examinationsmentioning
confidence: 99%
“…Furthermore, inadequate FSG has been associated with subsequent colorectal cancer (3, 4). Previous studies, largely single institution experience with relatively small numbers of patients, have suggested that older individuals and women are more likely to have inadequate FSG, but there is limited information on other factors that may be associated with inadequate FSG (5, 6).…”
Section: Introductionmentioning
confidence: 99%